Conventional Plastics' Harmful Effects and Biological and Molecular Strategies for Biodegradable Plastics' Production - Edaes, Felipe S.; de Souza, Cleide B. (Current Biotechnology, 2020)
Background: Plastic materials are ubiquitous and, despite the great benefits and advantages that the materials provide to human beings and society, their harmful effects are remarkable. Plastics’ ingestion is harmful and can occur through microplastics and their by-products (BPA and DEHP). It can trigger health problems. Also, the material decomposition time is significant and consequently, plastic waste accumulates in the environment, posing a major problem to fauna and flora. Objectives: The aim of this study is to develop a review of conventional plastics’ negative aspect in human and environmental life, as well as to study the existing biological and molecular strategies for the production of biodegradable plastics, making a comparison of their advantages over conventional plastics, in favor of socio-environmental welfare. Methods: In this review, articles published in the last 20 years related to different aspects of conventional plastics and biodegradable plastics were accurately analyzed and reviewed. The subjects addressed ranged from conventional plastics and the problems related to their large-scale production, as well as biodegradable plastics, their advantages and the most recent advances in the development of production methods and improvement of these biopolymers were extensively reviewed and discussed concisely. Results: The present study demonstrated that, among the biopolymers discussed, thermoplastic starch (TPS) is the most promising one due to its low cost, being one of the best materials to provide a viable alternative in the search for biodegradable plastics. Polylactic acid (PLA) presents the greatest potential for future medical applications due to its unique physicochemical properties and the possibility of being used in 3D printing techniques.Polyhydroxyalkanoates (PHAs) have the greatest commercial potential in replacing fossil fuel-based plastics because of their similar properties to conventional plastics and because they are synthesized by microorganisms from renewable carbon sources. Conclusion: This study demonstrated the various harmful effects that the large-scale use and improper disposal of conventional plastic materials generated to the environment and human health, and proposed an alternative to this problem, the biodegradable plastics. Although this study presented three promising biodegradable plastics (TPS, PLA and PHAs), as well as described their production methods, there are currently no viable biodegradable plastic polymers that can be used for the total replacement of conventional plastics, especially from an economic perspective. However, in the future, modifications in the production methods and chemical structures of these polymers will allow the replacement of conventional plastics by biodegradable plastics, as well as a more extensive application of these biopolymers.
Keywords: Environment